Micro-CT Evaluation of Four Root Canal Obturation Techniques - Kalantar Motamedi, Mahmood Reza (Scanning, 2021)
PURPOSE: The aim of this in vitro study was to evaluate the quality of four root canal obturation techniques using microcomputed tomography (micro-CT). MATERIALS AND METHODS: A total of 36 mandibular first premolars with mostly round canals were decoronated, then instrumented up to a size F3 rotary file, and dressed with an epoxy resin-based sealer. Subsequently, they were divided into 4 different groups (n = 9) based on the method of obturation: lateral condensation using 0.02 tapered master cone (LC2), lateral condensation using 0.04 tapered master cone (LC4), matched single-cone technique (MS), and matched single cone-mediated ultrasonic activation (MSUA). All the teeth were scanned using micro-CT (resolution of 19 μm), and the percentage volume of voids was calculated. One-way analysis of variance and Tukey test were used to analyze the data (α = 0.05). RESULTS: The total percentage volume of voids was significantly lower in the MSUA group compared to all other groups (P < 0.05). The total percentage volume of voids was significantly lower in the MS group compared to the LC4 (P < 0.001) and LC2 (P < 0.001) groups. However, there was no significant difference between the LC2 and LC4 groups (P < 0.65). CONCLUSIONS: MSUA, significantly, showed the least root canal filling voids amongst all the obturation techniques studied. MSUA can be considered an effective method for the filling of the round root canals. In general, lateral condensation using either 0.02 or 0.04 tapered master cones had significantly the highest volume percentage of voids amongst the experimental groups.